Relationship of Secondary School Mathematics Achievement with Engineering Mathematics 2 in Polytechnics - Husnira Binti Hussin; Marina Binti Majid; Rohayu Binti Ab Wahab (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
Engineering Mathematics 2 is one of the core courses for all diploma-level engineering students in Malaysian Polytechnic. From the statistics obtained, students achievement in the Engineering Mathematics 2 course (DBM2013) is still moderate and less satisfactory. This is because the subject of Engineering Mathematics 2 is mostly related to calculus and only students who have taken Additional Mathematics subject during secondary school had a basic in the Engineering Mathematics 2. Thus, this research was developed to see the relationship and influence of Mathematics subject during secondary school level, especially Additional Mathematics with the subject of Engineering Mathematics 2 in Polytechnic. High school achievement was measured using the Sijil Pelajaran Malaysia (SPM) examination results in Additional and Modern Mathematic subjects. Meanwhile, the results in the polytechnic level were measured from the final result of the Engineering Mathematics 2 course. The research used secondary data obtained from the examination unit from 2442 students of Semester 2 of Diploma in Civil Engineering (JKA), Diploma in Electrical Engineering (JKE) and Diploma in Mechanical Engineering JKM) at Polytechnic Sultan Mizan Zainal Abidin (PSMZA). Data obtained were processed and analyzed using Microsoft Excel 2010 and Statistical Packages For Social Sciences (SPSS) version 23.0 through Easy Linear Regression Analysis. The findings from the regression analysis showed that there was a significant positive correlation between the achievement of Mathematics during secondary schools with the achievement of Engineering Mathematics 2 in polytechnics and it also proved that Additional Mathematics is one of the medium for student’s excellence in Engineering Mathematics 2 at polytechnics.